Effects of temperature and inoculation ratio on methane production and nutrient solubility of swine manure anaerobic digestion. (March 2020) - Cao, Leipeng; Keener, Harold; Huang, Zhenghua; Liu, Yuhuan; Ruan, Roger; Xu, Fuqing
Graphic abstract: Highlights: Mesophilic condition was optimal temperature for AD of swine manure. The maximum cumulative CH4 yield was obtained with F/I ratio of 2.0 and 3.0. With increase of F/I ratio, the lag phase increased while reaction rate decreased. AD increased solubility of N, Cu, and Zn while decreased that of P. Changes of nutrient solubility were generally more significant at high F/I ratio. Abstract: This study investigated the effects of temperature and volatile solids (VS) ratio of feedstock to inoculum (F/I ratio) on methane (CH4 ) production and the solubility of nitrogen (N), phosphorus (P), cooper (Cu), and Zinc (Zn) after anaerobic digestion (AD) of swine manure. The highest cumulative CH4 yield of 470 L/kgVSfeed was obtained with F/I ratios of 2.0 and 3.0 with mesophilic (37 °C) temperature, and methane production rate decreased with the increase of F/I ratio. As F/I ratio increased from 0.5 to 4.0, the lag phase for methane production increased from 1.02 days to 13.52 days, indicating an initial inhibition at high F/I ratios. AD increased the concentrations of ammonia, Cu and Zn in the AD effluent supernatant, while decreased total and water extractive P concentrations. The changes of ammonia, Cu, Zn, and P concentrations were more significant with the increase of F/I ratio.